An Ethical Approach to AI in a Post-Human Epoch - Singh, Gurman; Sharma, Mamta (Journal of Information and Knowledge, 2024)
A common ethical apprehension regarding artificial intelligence seems to centre around fears that it may endanger the human condition, ‘what it means to be human.’ It is thought that radical advancements in AI might irreversibly alter the experiential grounds of humanity. However, we contest that mankind, as a unified semiotic system of signs and values that anchored the Enlightenment view of the world, has been adequately critiqued and deconstructed over the past few decades. It is within this post-Enlightenment, and more importantly, post-human, context that we may engage with technological advancements in the fields of AI, IT, genetics, virtual reality, etc. Contemporary literature on AI ethics has engaged with the question of artificial intelligence through the perspective of automation and algorithms, situating machine- and deep-learning within the history of man’s endeavours to automate labour: tied to the historical practicalities of social forces, originating in the ‘general intellect’ and ancient practices, formalized over time. In effect, artificial intelligence serves to codify, automate and perfect human labour. By co-opting this conceptual framing, we can quell much of the alarmist rhetoric that greets the topic of AI. It is also the framework within which we can approach the ethic of implementing AI systems in academic and professional environments: as the fruits, and by extension the general inheritance of mankind. At the same time, we must also contend with the ontological frontiers represented by artificial intelligence, and virtuality in general. Even as the wheel, the horse and language accelerated the development of Bronze Age cultures, these technological frontiers today promise to inaugurate radical new futures for mankind. This makes it all the more expedient for us to critically engage with the ethical dimensions of AI in everyday life. As such, the existential and ethical aspects of AI cannot be approached without first reckoning with the ‘technological mode,’ a product of man’s inherent techne. This mode, which has propelled man from prehistory to modernity, has wielded both liberatory and despotic velocities. In deterritorializing traditional systems of social organisation and production, it enabled the reorganization of society along the logic of industrialization and commerce, the pluralized proliferation of information, as well as a deconstruction and revaluation of the very notions of the ‘natural,’ the ‘human,’ and the ‘real.’ To borrow from Donna Haraway: perhaps, we have not become, but always have been, cybernetic organisms. Lastly, we must remain vigilant against the burgeoning ‘metaphysics of technology,’ of replacing the metaphysical grounds of faith with technology. A rational, scientific temper must guide our forays into the most radical advancements in AI, keeping quasi-theological passions at arm’s length.